PENERAPAN MODEL PEMBELAJARAN BERBASIS LINGKUNGAN DALAM UPAYA MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA SMA METRO - Cholvistaria, Mia (Bioedukasi Jurnal Pendidikan Biologi, 2012)
The aims of the study was to apply the environment based learning model in an effort to improve students science process skills. The research was conducted by the classroom action research on class X2 SMAN 2 Metro academic year 2011/2012 indicated that students science process skills still have not shown good results. Because the achievement still under 50% with the percentage of students who reach the KKM (â¥ 70%). The curriculum is currently implemented of KTSP where the teachers are required to be able to manage with the student centered learning. One model of learning which are student centered learning is environment based learning model. The results show that the science process skills increase from 50.00% to 79.45% increase of 29.45%. Based on the results of research can be concluded that the study uses a model-based learning environment can improve the skills sains process.Â Kata kunci:Â  Pembelajaran Berbasis Lingkungan, Keterampilan Proses Sains